Specialized, multi‐component care for individuals with first‐episode psychosis: Effects on autonomy, competence and relatedness. Issue 6 (15th January 2019) - Breitborde, Nicholas J. K.; Pine, Jacob G.; Moe, Aubrey M.
Abstract : Aim: Self‐determination theory (SDT) has demonstrated that human well‐being is associated with the satisfaction of three basic psychological needs (ie, autonomy, competence and relatedness)—with more recent research highlighting the applicability of SDT to individuals with first‐episode psychosis (FEP). These findings suggest that satisfaction of basic psychological need may be an important treatment target for specialized clinical programs for FEP. Methods: We examined the effects of participation in specialized, multi‐component care for FEP on basic psychological need satisfaction. Results: After 6 months of treatment, individuals with FEP experienced gains in autonomy and relatedness and a near significant improvement in competence. Conclusions: Although our results should be interpreted cautiously given the uncontrolled study design and small sample size, our data suggest that the benefits of participation in comprehensive, early intervention for psychotic disorders may include increased satisfaction of basic psychological needs.